2020
DOI: 10.1097/qco.0000000000000620
|View full text |Cite
|
Sign up to set email alerts
|

Host–vaginal microbiota interactions in the pathogenesis of bacterial vaginosis

Abstract: Purpose of Review-The etiology of BV, the most common cause of vaginal discharge in women, remains controversial. We recently published an updated conceptual model on BV pathogenesis, focusing on the roles of G. vaginalis and Prevotella bivia as early colonizers and Atopobium vaginae and other BVAB as secondary colonizers in this infection. In this paper, we extend the description of our model to include a discussion on the role of host-vaginal microbiota interactions in BV pathogenesis.Recent Findings-Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(127 citation statements)
references
References 57 publications
3
102
0
9
Order By: Relevance
“…Bacterial vaginosis can be diagnosed by Amsel criteria, Gram staining, Nugent score, and molecular assays [ 40 , 92 ]. It is usually accompanied by a significant number of G. vaginalis , Prevotella species, A. vaginae , Sneathia species, and other BVAB as a result of disrupted vaginal microbiota [ 93 , 94 ]. Frequently, BV is associated with elevated risk of HIV acquisition, miscarriage, pelvic inflammatory diseases, preterm labour, postpartum endometritis, and STIs acquisition [ 90 , 95 97 ].…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%
“…Bacterial vaginosis can be diagnosed by Amsel criteria, Gram staining, Nugent score, and molecular assays [ 40 , 92 ]. It is usually accompanied by a significant number of G. vaginalis , Prevotella species, A. vaginae , Sneathia species, and other BVAB as a result of disrupted vaginal microbiota [ 93 , 94 ]. Frequently, BV is associated with elevated risk of HIV acquisition, miscarriage, pelvic inflammatory diseases, preterm labour, postpartum endometritis, and STIs acquisition [ 90 , 95 97 ].…”
Section: Indigenous Vaginal Microbiota In Womenmentioning
confidence: 99%
“…The major drawbacks for the development of new diagnostic assays for BV are the lack of a uniform case definition for BV and that the etiology of BV remains poorly understood (Forsum et al, 2005;Muzny and Schwebke, 2016). In recent years, the advancement of molecular and high-throughput sequencing technologies [e.g., next-generation sequencing (NGS)] has revealed that BV is a multifactorial condition influenced by social, epidemiological, microbiological and host factors (Muzny and Schwebke, 2016;Muzny et al, 2020). Also, evidence suggests that the presence of a polymicrobial biofilm offers protection for many BV-associated bacteria against hydrogen peroxide (H 2 O 2 ), antibiotics and host immunity (Swidsinski et al, 2005(Swidsinski et al, , 2008(Swidsinski et al, , 2015Patterson et al, 2007) and these factors should be considered when designing a POC test.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings by Muzny et al show that despite the high abundance of G. vaginalis and P. bivia in women with BV, neither induced a robust inflammatory response from vaginal epithelial cells, suggesting that these pathogens are early colonizers evading the immune system while establishing the BV biofilm. As a result, secondary colonizers, including A. vaginae, Sneathia spp., and other BVAB, act as more potent stimulators of the hos-immune response to BV, leading to the signs, symptoms, and its adverse effects [2]. The treatment of BV in symptomatic women has been established with metronidazole or clindamycin.…”
Section: Discussionmentioning
confidence: 99%